Pre-malignant nature of congenital cystic adenomatoid malformation: a case study and imaging characteristics - Liu, Yifan (International Surgery Journal, 2025)
Congenital cystic adenomatoid malformation (CPAM) is uncommon developmental anomaly that is often diagnosed in routine prenatal ultrasound. It has various subtypes described by Stocker et al, each with its own characteristics. Patients with symptomatic CPAM are treated surgically while those that are asymptomatic are sometimes management with surveillance only. In this report, a case study of non-malignant type 1 CPAM was managed surgically with histology demonstrating KRAS mutation, linking its potential for malignant transformation as described in literature.